2016
DOI: 10.1021/acs.iecr.5b04383
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent (Binary and Ternary) Adsorption Equilibria of Volatile Organic Compounds (Acetone, Toluene, and n-Hexane) on Activated Carbon in Supercritical Carbon Dioxide

Abstract: The multicomponent (binary and ternary) adsorption equilibria of three volatile organic compounds (VOCs) (acetone, toluene, and n-hexane) on activated carbon were studied under supercritical carbon dioxide (scCO 2 ) conditions. The multicomponent adsorption equilibrium data were obtained at 313−353 K and 4.2−10.0 MPa and depended on the affinities of the adsorbates for the adsorbent. The amounts of adsorbed VOCs decreased with increases in the pressure and decreases in the temperature, owing to the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Adsorption of VOCs from the gas and liquid phases has been the focus of scientific research but often involves only one component. , For single-component experiments, fixed bed adsorption is characterized based on the Thomas, bed depth service time, and Yoon–Nelson models, obtaining a high degree of fit between experimental data and model values. , Studies in the related literature have indicated that during the adsorption of VOC mixtures, competitive adsorption occurs, i.e., a phenomenon involving the displacement of molecules of one adsorbate from the adsorption bed by molecules of another adsorbate. For binary VOC mixtures, the breakthrough curves can be divided into characteristic areas: (1) the outlet concentrations of both components are close to zero; (2) the mass transfer zone of the component with a lower adsorption affinity reaches the outlet of the adsorption column; (3) the outlet concentration of the less adsorbed component exceeds the value of its inlet concentration (displacement from the bed by the component with a higher adsorption affinity); (4) the mass transfer zone of the better-adsorbed component reaches the column outlet, and the outlet concentration of the component increases; and (5) the adsorption bed is completely saturated, and the outlet concentrations are close to the initial concentrations …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of VOCs from the gas and liquid phases has been the focus of scientific research but often involves only one component. , For single-component experiments, fixed bed adsorption is characterized based on the Thomas, bed depth service time, and Yoon–Nelson models, obtaining a high degree of fit between experimental data and model values. , Studies in the related literature have indicated that during the adsorption of VOC mixtures, competitive adsorption occurs, i.e., a phenomenon involving the displacement of molecules of one adsorbate from the adsorption bed by molecules of another adsorbate. For binary VOC mixtures, the breakthrough curves can be divided into characteristic areas: (1) the outlet concentrations of both components are close to zero; (2) the mass transfer zone of the component with a lower adsorption affinity reaches the outlet of the adsorption column; (3) the outlet concentration of the less adsorbed component exceeds the value of its inlet concentration (displacement from the bed by the component with a higher adsorption affinity); (4) the mass transfer zone of the better-adsorbed component reaches the column outlet, and the outlet concentration of the component increases; and (5) the adsorption bed is completely saturated, and the outlet concentrations are close to the initial concentrations …”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problem of pollutants emitted from cold start of automobiles, molecular sieve materials with good texture and adsorption performance have gradually attracted researchers' attention. ZSM-5, 20 BETA, 21 and MCM-41 22,23 are commonly used for VOCs adsorption emitted from automobiles. Furthermore, in addition to being used as adsorbent, bimetallic catalysts containing platinum and base metal oxide supported on MCM-41 also have good catalytic oxidation activities for ethanol with T50 less than 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…As an important predecessor of submicron particles (PM2.5) and ozone pollution in the atmosphere, volatile organic compounds (VOCs) emitted from industrial manufacturing have received increasing attention in recent years [ 1 , 2 ]. Among the VOCs, the benzene series (BTEX) and acetone have always been simultaneously utilized in paints, solvents, and raw materials in the chemical and printing industry [ 3 , 4 , 5 ]. Exposure usually causes a number of environment-related health problems, including dizziness, nausea, organ damage, and even cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%